Different Views of Textual « Aboutness »: A Recipient Evaluation of the Content Descriptors Proposed by Professional Indexers, Authors, Readers and Corpus Analysis Tools - Bowker, Lynne; Mackay, Rebecca; Ciro, Jairo Buitrago; Kasama, Deni (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
As an increasing number of groups – professional indexers, authors, readers, and even automated tools such as corpus analysis software – tackle the challenge of describing document contents, the time is right to conduct a recipient evaluation of these different key words to see which ones users perceive to be the most helpful for identifying relevant materials. Un nombre croissant de groupes — indexeurs professionnels, auteurs, lecteurs, et même des outils automatisés tels que les logiciels d’analyse de corpus, relèvent le défi de décrire les contenus de documents, et le moment est venu de procéder à une évaluation du destinataire de ces différents mots-clés pour voir lesquels sont perçus par les utilisateurs comme les plus utiles pour identifier des matériaux pertinents.